Analisis Perbedaan Return Saham, Trading Volume Activity Dan Bid-Ask Spread Sebelum Dan Sesudah Stock Split: (Studi Kasus Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2017 – 2021) - Fajar Irvangi; Hani Fitria Rahmani (MAMEN: Jurnal Manajemen, 2022)
This study aims to determine the differences in stock returns, trading volume activity and bid-ask spreads before and after the stock split in companies listed on the Indonesia Stock Exchange for the period 2017-2021. The population in this study were all companies listed on the Indonesia Stock Exchange that carried out a stock split during the period 2017-2021. Sampling using purposive sampling method, based on predetermined criteria obtained a sample of 30 companies. The method used is a different test analysis with an observation period of 10 days and 20 days, namely t = -5 (5 days before the stock split), t = +5 (5 days after the stock split), t = -10 (10 days before the stock split). split) and t = +10 (10 days after stock split). Hypothesis testing was carried out with the Paired Sample T-Test for data that was normally distributed and the Wilcoxon Signed Rank Test for data that were not normally distributed. Based on the results of the study, it was found that there were no differences in stock returns before and after the stock split, there were differences in trading volume activity before and after the stock split, and there were differences in bid-ask spreads before and after the stock split.